Garbage Citizenship: Vital Infrastructures of Labor in Dakar, Senegal , Rosalind Fredericks (2018) - (:unkn) unknown (My University, 2021)
Review of: Garbage Citizenship: Vital Infrastructures of Labor in Dakar, Senegal , Rosalind Fredericks (2018)Durham: Duke University Press, 216 pp.,ISBN 978-1-47800-141-6, p/bk, $23.95
Keywords: African Research